Imperfect crowding adaptation of mammalian cells towards osmotic stress and its modulation by osmolytes. Issue 11 (20th September 2017) - Gnutt, David; Brylski, Oliver; Edengeiser, Eugen; Havenith, Martina; Ebbinghaus, Simon
Abstract : The short-term adaptation of cellular crowding after osmotic stress is imperfect but can be modulated by the osmolyte TMAO. Abstract : Changes of the extracellular milieu could affect cellular crowding. To prevent detrimental effects, cells use adaptation mechanisms to react to such conditions. Using fluorescent crowding sensors, we show that the initial response to osmotic stress is fast but imperfect, while the slow response renders cells more tolerant to stress, particularly in the presence of osmolytes.